2012
DOI: 10.4236/abb.2012.327121
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage levels in systemic lupus erythematosus patients with low disease activity: An evaluation by comet assay

Abstract: Oxidative stress has been implicated in the inflammatory process of Systemic Lupus Erythematosus (SLE), particularly by the formation of anti-DNA autoantibodies, which can lead to DNA damage. The aim of this study was to investigate, through comet assay, whether the level of DNA damage in SLE patients is different from that of healthy subjects. Twenty-five adult SLE patients with SLEDAI up to ten, and 25 healthy subjects were paired according to age, gender and Body Mass Index (BMI). Other anthropometric varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…This is the first study to use a buccal micronucleus cytome assay to identify potential biomarkers associated with SLE. Interestingly, this study showed a statistically significant and clinically relevant increase in levels of biomarkers of DNA damage (micronuclei) in patients as compared to controls, which supports results of several studies that used other methods to assess DNA damage, including a comet assay (), a colony survival assay, and kinetics of phosphorylation of structural maintenance of chromosomes protein 1 (). Micronuclei are formed mainly from chromatids or chromosome fragments, which remain excluded from the main cell nucleus following mitosis ().…”
Section: Discussionsupporting
confidence: 86%
“…This is the first study to use a buccal micronucleus cytome assay to identify potential biomarkers associated with SLE. Interestingly, this study showed a statistically significant and clinically relevant increase in levels of biomarkers of DNA damage (micronuclei) in patients as compared to controls, which supports results of several studies that used other methods to assess DNA damage, including a comet assay (), a colony survival assay, and kinetics of phosphorylation of structural maintenance of chromosomes protein 1 (). Micronuclei are formed mainly from chromatids or chromosome fragments, which remain excluded from the main cell nucleus following mitosis ().…”
Section: Discussionsupporting
confidence: 86%
“…In fact elevated MDA levels and reduced TAS levels also point towards a state of oxidative stress. Shah et al [9] have recently reported inflammatory response in SLE which aggravates oxidative stress with potential to provoke damage to lipids, proteins and DNA [12,13]. The observations of the present study on significantly increased genomic damage also find reflections in the results documented by Montalvao et al [13] who reported 1.3x significantly increased (p=0.000) DNA damage index in 25 SLE patients compared to the value in equal number of healthy controls.…”
Section: Discussionsupporting
confidence: 82%
“…The inflammatory response in SLE exacerbates oxidative stress [9] which tends to promote cellular macromolecular damage, lipid peroxidation and protein oxidation [10,11] and damage to DNA [12,13]. Health can further be compromised as any unrepaired DNA damage can initiate neoplasia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Determinations of DNA damage and DNA damage responses is rapidly expanding in research related to disease states [ 38 – 40 ] and in the investigation of the specific mechanisms of action of ionizing radiation, viral infections, and chemotherapeutic drugs [ 41 – 45 ] but is currently less understood in cryobiology. There is also an ever-increasing understanding of the mechanisms by which endogenous DNA damage signals can activate innate immune responses, especially effects mediated by increased expression of interferons [ 46 51 ].…”
Section: Discussionmentioning
confidence: 99%